Гіпоксія як модулюючий чинник капацитації та кріорезистентності сперматозоїдів людини - Petrushko, Maryna; Yurchuk, Taisiia (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2026)
Despite increasing interest to the role of hypoxia in reproductive processes, its impact on sperm capacitation and cryoresistance remains insufficiently described. This study investigated the effect of oxygen tension during pre-cryopreservation sperm incubation on the capacitation efficiency and examined the relationship between capacitation and cryoresistance. According to the WHO criteria, ejaculates from 30 healthy normozoospermic men were analyzed. Functional characteristics and cryoresistance of spermatozoa were assessed after density gradient processing and in vitro capacitation under 1, 5 and 21% oxygen concentrations. An incubation of human spermatozoa under moderate hypoxia was found to positively influence the viability, motility, and capacitation activation. For the first time, we have demonstrated that oxygen tension during in vitro incubation is a critical factor determining sperm survival following thawing. These findings suggest that moderate hypoxia may represent a promising biotechnological strategy to improve sperm cryopreservation protocols and enhance the efficiency of assisted reproductive technologies. Probl Cryobiol Cryomed. 2025; 35(4): 219—223